HYBRID SOLAR LIGHTING SEBAGAI ALTERNATIF TEKNOLOGI PENERANGAN ALAMI BANGUNAN UNTUK EFISIENSI ENERGI DAN PEMANFAATAN ENERGI TERBARUKAN - Anggoro, Suryo (Jurnal Teknologi Lingkungan, 2009)
Artificial (electric) and direct lighting technologies available today have thepotential to greatly reduce the growth rate of electricity consumed through lightingworldwide. While electric lighting has been inefficient throughout much of itshistory, direct (natural) lighting is nearly free and often plentifully supplied by thesun. However, electric lighting systems are necessary when solar lighting is notadequate and these technologies are being greatly improved.One relatively new method of lighting a building’s interior combines both artificialand direct lighting to maximize efficiency is accomplished through the use of aparaboloidal, mirrored dish which actively tracks the sun to concentrate sunlightinto an array of fiber optics.